2010
DOI: 10.1364/ol.35.001479
|View full text |Cite
|
Sign up to set email alerts
|

Coherent optical link through the turbulent atmosphere

Abstract: We describe the realization of a 5 km free-space coherent optical link through the turbulent atmosphere between a telescope and a ground target. We present the phase noise of the link, limited mainly by atmospheric turbulence and mechanical vibrations of the telescope and the target. We discuss the implications of our results for applications, with particular emphasis on optical Doppler ranging to satellites and long-distance frequency transfer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 11 publications
2
60
0
1
Order By: Relevance
“…11 (b), where continuous frequency measurement over several minutes shows a consistently low frequency fluctuation. More recently, Djerroud et al have reported a coherent optical link across 5 km of turbulent atmosphere based on a cw Nd:YAG laser (Djerroud et al, 2010). A remarkably low Allan deviation of 1.3×10 -14 is achieved at 1 s, and the stability further improves to 2×10 -15 at 100 s. The authors, however, did point out that the experiment took place at an observatory 1323 m above the sea level, which could account, at least in part, for the high degree of frequency stability over a long distance.…”
Section: Discussionmentioning
confidence: 99%
“…11 (b), where continuous frequency measurement over several minutes shows a consistently low frequency fluctuation. More recently, Djerroud et al have reported a coherent optical link across 5 km of turbulent atmosphere based on a cw Nd:YAG laser (Djerroud et al, 2010). A remarkably low Allan deviation of 1.3×10 -14 is achieved at 1 s, and the stability further improves to 2×10 -15 at 100 s. The authors, however, did point out that the experiment took place at an observatory 1323 m above the sea level, which could account, at least in part, for the high degree of frequency stability over a long distance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, remote distribution of optical-frequency references has attracted considerable interest [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. There are in general two possible transfer media: optical fiber and free space.…”
Section: Introductionmentioning
confidence: 99%
“…Coherent optical links spanning well over 100 km have been experimentally demonstrated by a number of groups [5][6][7][8][9]. On the other hand, free-space clock distribution benefits from its flexibility and low overhead cost, and has proved to be a feasible option for short-distance, ad hoc networks or networks among mobile hubs, despite its much poorer link fidelity due primarily to air turbulence [15][16][17][18][19]. It is also the only option for space-terrestrial network synchronization [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent papers study fluctuations in laser propagation on distances going to dozens of kilometres [1][2][3]. To measure influence of atmosphere, the received beam is mixed with a delayed version and frequency downshifted of the transmitted wave.…”
Section: Introductionmentioning
confidence: 99%